PALAEOCLIMATIC EVOLUTION IN LOUTRA ARIDEAS CAVE (ALMOPIA SPELEOPARK, MACEDONIA, N. GREECE) BY STABLE ISOTOPIC ANALYSIS OF FOSSIL BEAR BONES AND TEETH - Zisi, N.; Dotsika, E.; Tsoukala, E.; Giannakopoulos, A.; Psomiadis, D. (Bulletin of the Geological Society of Greece, 2010)
Carbon and oxygen stable isotope values (δ13C, δ18O) were obtained from structural carbonate in the bioapatite of bear bones (Ursus ingressus) from Loutra Arideas cave, Almopia Speleopark, Macedonia, N. Greece. Samples of Late Pleistocene bear bones were studied for palaeoclimatic reconstruction of the area. The age range of the fossil layers is from 32ka BP to a maximum of 38ka BP. Generally, the palaeoclimatic proxy is correlated with literature data for climatic variations in the area during Late Pleistocene, whereas dietary behavior was investigated taking into account possible diagenetic processes that may have affected the carbonate matrix of the bones.